Value of ultrasonography in the diagnosis of carpal tunnel syndrome—a new ultrasonographic index in carpal tunnel syndrome diagnosis: A clinical study - Perţea, Mihaela (Medicine (Baltimore), 2020)
We analyze the effectiveness of ultrasonography in diagnosing carpal tunnel syndrome (CTS) and propose the use of sonographic index of median nerve (MN) in carpal tunnel (SIMNCT) in a diagnostic algorithm and in establishing a scale of severity. We studied a group of 344 patients with CTS symptoms, examining them by ultrasound. We measured in all patients, on the affected hand: the size of the cross-sectional area of the MN at carpal tunnel (CT) inlet and outlet, nerve morphology at passage through CT, the vertical thickness of the MN entering into the CT – G1, the lowest vertical thickness into the CT or leaving the CT – G2, the thickness of the MN in the transversal plane as entering in the CT – L. Normal values were considered the similar measurements taken on the healthy hand and we established as normal SIMNCT = 16%. We proposed the formula SIMNCT = 100% (1-G2/G1) in order to calculate the index. Statistics show a significant sensitivity of SIMNCT (P < .0001) compared with cross-sectional area (CSA) and flattening ratio in the diagnosis of CTS. Analyzing the SIMNCT developed by us, we demonstrated a sensitivity of 94.81% and a specificity of 99.66% in CTS diagnosis. Thereby, we propose a CTS severity classification: normal = 16%, mild = 16–19%, moderate = 19% to 28%, severe = 28% to 50%, very severe > 50%. Ultrasonography is an effective method of studying the morphology of the tunnel and compressed nerve at various CTS stages and determining the cause of compression. The SIMNCT is a valuable and practical indicator and it can be used in the CTS diagnosis.